Genetics of Inherited Retinal Diseases in Understudied Ethnic Groups in Italian Hospitals - Maltese, Paolo Enrico; Colombo, Leonardo; Martella, Salvatore; Rossetti, Luca; El Shamieh, Said; Sinibaldi, Lorenzo; Passarelli, Chiara; Coppè, Andrea Maria; Buzzonetti, Luca; Falsini, Benedetto; Chiurazzi, Pietro; Placidi, Giorgio; et al. (Frontiers in Genetics, 2022)
Purpose: Describing the clinical and genetic features of an ethnically heterogeneous group of (inherited retinal diseases) IRD patients from different underrepresented countries, referring to specialized Italian Hospitals, and expanding the epidemiological spectrum of the IRD in understudied populations. Methods: The patients’ phenotypes underwent were characterized by exhaustive ophthalmological examinations, including morpho-functional testing. Genetic testing was performed using next-generation sequencing (NGS) and gene sequencing panels targeting a specific set of genes, Sanger sequencing and—when necessary—multiplex ligation-dependent probe amplification (MLPA) to better identify the genotype. When possible, segregation analysis was performed in order to confirm unsolved cases. Results: The article reports the results of the phenotypes and genotypes of 123 IRD probands, 69 males and 54 females, mean age 41 (IQR, 54-30) years, disease onset at 13 (IQR, 27.25-5) years. Thirty-three patients out of 123 (26.8%) were Africans (North/Northwest Africa), 21 (17.1%) Asians, 19 (15.4%) Americans (South/Central America) and 50 (40.7%) Europeans (Eastern Europe). Retinitis pigmentosa was the most represented phenotype (56%), followed by cone dystrophy (11%) and Leber congenital amaurosis (7%), while ABCA4 was the most frequently mutated gene (18%), followed by USH2A (9%) and RPGR (5%). About ABCA4 variants found in Stargardt disease, macular and cone dystrophies were predominant in Asian (42%) and European (21%) patients. The most represented inheritance pattern was autosomal recessive, while a higher frequency of homozygous patients versus compound heterozygotes as compared to previous studies on Italian IRD patients was evidenced, reflecting a possible higher frequency of inbreeding marriages. Conclusion: Though limited by the relatively low number of patients, the present paper paints a picture of the clinical and genetic features of IRD patients from understudied ethnic groups referred to Italian specialized hospitals and extended the epidemiological studies on underrepresented world regional areas.